2015
DOI: 10.1002/hbm.22911
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal traits of psychopathy linked to reduced integrity of the uncinate fasciculus

Abstract: Psychopathy is a personality disorder characterized by callous lack of empathy, impulsive antisocial behavior, and criminal recidivism. Here we performed the largest diffusion tensor imaging (DTI) study of incarcerated criminal offenders to date (N = 147) to determine whether psychopathy severity is linked to the microstructural integrity of major white matter tracts in the brain. Consistent with the results of previous studies in smaller samples, we found that psychopathy was associated with reduced fractiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
61
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 38 publications
12
61
1
1
Order By: Relevance
“…In this study, the brain abnormality of ASPD appear in both temporal and frontal lobes, which is consistent with prior studies in aggression-prone individuals (Sundram et al 2012; Wolf et al 2015; Hoppenbrouwers et al 2013). Certain types of antisocial activities are closely linked with frontal-temporal dysfunction, with joint abnormalities of the two regions predisposing some patients to antisocial behaviors (Miller et al 1997).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, the brain abnormality of ASPD appear in both temporal and frontal lobes, which is consistent with prior studies in aggression-prone individuals (Sundram et al 2012; Wolf et al 2015; Hoppenbrouwers et al 2013). Certain types of antisocial activities are closely linked with frontal-temporal dysfunction, with joint abnormalities of the two regions predisposing some patients to antisocial behaviors (Miller et al 1997).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, an impaired emotion-cognition interaction in psychopaths is involved in changed prefrontal and temporal brain activation (Muller et al 2008b). As a result of these findings, some studies have put forward theories that fronto-temporal brain abnormalities are associated with antisocial behavior disorders (Blair and Mitchell 2009), which were verified continuously (Sundram et al 2012; Wolf et al 2015; Hoppenbrouwers et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, these analyses yielded a high intraclass correlation ( r = .99) for PCL-R total scores; Factor scores (Factor 1, r = .92; Factor 2, r = .89) and Facet scores (Facet 1, r = .88; Facet 2, r = .99; Facet 3, r = .80; Facet 4, r = .88). This is consistent with previously reported PCL-R inter-rater reliabilities from our research group (Dargis et al, 2015; Philippi et al, 2015; Wolf et al, 2015). 40% of the current sample met criteria for psychopathy (PCL-R score ≥30).…”
Section: Methodssupporting
confidence: 93%
“…Those studies showed a positive link between increased neuroticism and psychopathy-related traits (e.g. lying, manipulativeness, egocentricity), and reduced WM integrity in the uncinate fasciculus, the forceps minor, the corona radiata, the superior longitudinal fasciculus, and the inferior frontooccipital fasciculus (48,49). No published study has, however, investigated the association between WM and personality traits in BD.…”
Section: Introductionmentioning
confidence: 95%